Role of social spaces in Mixed use developments in optimizing Social sustainability at neighborhood level –Comparative study: Exploring the Impact of Social Spaces in Mixed Use Developments (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The current paper looks at exploring the need to identify “Social spaces” and “Socialinteractions”based on such social spaces in context to the changing urban scenarios at the scale ofmixed use neighbourhoods today and the potential of these neighbourhoods in optimising the socialsustainability for „spatially dependant user group‟(group of people dependant on neighbourhood spacesfor social exchanges).Significance of research In Context of changing Urban Scenarios ,the impacts of changes in the builtunbuiltrelationships and changed formats in social exchanges ,will need redefining what is” Socialspace” and hence a need to identify typologies within neighbourhood spaces which will play key role inoptimising social sustainability. The current research attempts towards understanding the factorsshaping this socio-spatial dynamix, for functional, liveable and sustainable Social spaces for thespatially dependant user group through comparative mapping and analysis of three different mixed useneighbourhoods to arrive at measuring how sustainable the given neighbourhood is with the currentstatus of how active and how much adequate the social spaces are are their impact in defining theoverall social sustainability of the neighbourhood.The literature review will investigate the concept of “Social sustainability”and be focused on how socialspaces conducive to social interactions in a mixed use neighborhood can be crucial in shaping socialsustainability.Through social surveys and interviews qualitative –quantitative mixed methods to arrive at needs andtypologies of different social spaces. The aim of this research will be to study how the built-unbuiltsocial infrastructure can be optimised to the changing societal needs of the “spatially dependant usergroup” ,enriched through new definitions of social connectivities , accessibilities and exchanges withinthe socio-spatial scale of mixed use neighborhoods.